P43 The prevalence and severity of chest pain in adults with congenital heart disease. (2nd March 2016) - Toumpourleka, M; Prapa, M; Kempny, A; Alonso-Gonzales, R; Swan, L; Gatzoulis, MA; Dimopoulos, K
Abstract : Keywords: chest pain, congenital heart disease, CCS score, coronary artery disease Background: Adults with congenital heart disease (ACHD) often present with chest pain (CP). Numerous potential causes for such pain have been described in this population, but the exact prevalence and relation to coronary artery disease (CAD) is still ill-defined. We assessed the prevalence and severity of CP in a consecutive group of ACHD outpatients, and report on the outcome of these patients. Methods: Consecutive patients seen in an ACHD outpatient clinic in a tertiary centre were recruited in this study. The presence of any CP was assessed and thereafter graded into 4 groups using the CCS score: 1- angina on strenuous or prolonged activity, 2- slight limitation, angina on vigorous activity, 3- moderate limitation, symptoms on everyday activities, 4- severe limitation, unable to perform activity or angina at rest. Patients with CP were followed-up and evidence of CAD or other coronary pathology was recorded. Results: A total of 199 patients were included in our study. Mean age was 37.8+-14.0 years and 61.4% were male. Congenital diagnoses included most types of ACHD, most commonly valvar disease (28, %), tetralogy of Fallot (20.6%), ASD (9.5%), aortic coarctation (9.5%) and VSD (9%). Complex anatomy was present in 6.0% and pulmonary hypertension in 3.5%. The vast majority of patients were in NYHA Functional class 1 (68.9%), with only 7.1% of patients in functional class 3 or 4. In the overall population, 33 patients reported CP (16.6%). In the majority of cases, this was mild (CCS class 1, 10.6% of all patients or 63.6% of patients with CP). In only in 9.1% of patients with CP was this moderate or severe (CCS 3 or 4). In the larger diagnostic groups, the prevalence of CP was: 17.9% in valvar disease, 12.2% in tetralogy of Fallot, 31.6% in ASD and 15.8 in aortic coarctation. We found no relation between the presence of risk factors (diabetes, hypercholesterolemia, hypertension, family history) and any CP; only current smoking was related to a CCS or 3 or above (p = 0.02). There was no relation between CP and cyanotic heart disease. Two patients with CP were known to have coronary anomalies, and one had had a diagnosis of myocardial infarction several years earlier, but with normal coronary angiography thereafter. In the overall population, 18 patients had undergone investigations for CAD prior to inclusion into the study, all of which had been negative. These included 5 patients who still complained of CP on inclusion to our study. After recruitment and over a median follow-up of 5 years, 19 patients (4 with CP on recruitment) required investigations specifically for CP (including 7 CT angiography and 5 invasive angiography): none demonstrated evidence of significant CAD. Moreover, 10 patients required hospitalisation for CP during follow-up, of which only one with CP on recruitment in the study. All were discharged without a diagnosis of CAD. Conclusions: As the ACHD population ages, the incidence of CAD will inevitably increase. Despite a high prevalence of CP in this ACHD cohort, few required investigations and none required intervention relating to CAD over 5 years of follow-up. CP alone is, thus, a poor marker of CAD in this cohort and a high level of expertise is required for the identification of CAD in this population. All cases with CP should be examined thoroughly for risk factors of CAD and the characteristics of the CP, to investigate and treat cases of true CAD in a timely fashion.